Household demand for fish in the Philippines quadratic almost ideal demand system approach - Temple, Devi Joy P.
Research studies that analyze demand for staple food such as rice, wheat, and corn are evident. However, very few align their focus on fish and its disaggregated demand, making it a relatively scarce discussin in countries like the Philippines. This study aims to analyze the demand for fish, specifically on the four most consumed fish types, namely bangus, tilapia, galunggong, and tuna. A Quadratic Almost Ideal Demand System (QUAIDS) was used to estimate the elasticities of demand for the four fish types. Elasticities of demand are then compared among househlds by location (urban vs rural) and poverty status (poor vs non-poor). The findings of this study show that galunggong, bangus, and tuna are considered normal goods for most households, while the other fish type (tilapia) is an inferior good. Also, tuna and bangus were found to be good substitutes for each other. Keywords: Fish, Demand, Quadratic Almost Ideal Demand System.